ERIC FONER'S "RECONSTRUCTION" AT TWENTY-FIVE. (19th December 2014) - Foner, Eric
<x content-type="archive" xml:space="preserve">Abstract</x> What follows is a written reproduction of a forum held at the annual meeting of the Organization of American Historians in San Francisco in April 2013. The forum commemorated the twenty-fifth anniversary of the publication of Eric Foner's Reconstruction: America's Unfinished Revolution, 1863–1877. Kate Masur (Northwestern University) organized and introduced the discussion, and the commentators in order of speaking were the following: Heather Andrea Williams, The University of Pennsylvania Gregory P. Downs, City College of New York and the Graduate Center of the City University of New York Thavolia Glymph, Duke University Steven Hahn, The University of Pennsylvania Eric Foner, Columbia University The written version on the following pages largely preserves the feel and tone of the original oral presentations by the contributors. However, given the opportunity for reflection inherent in the published word, the authors and editors have made some small changes to enhance readability.